(untitled) (Pregled: časopis za društvena pitanja / Periodical for social issues, 2017)
The coordination mechanism is indispensable in complex and unitary constitutional orders with a large number of regions and diversified administration. The representative democracy is governed by general legal acts, such as the Constitution and Law, and could be regulated by the internal executive branch‟s legal acts additionally. The B-H Constitution contains a general provision on the coordination mechanism and therefore is the first legal source of that mechanism. Pursuant to the European standards, another legal source in the legal acts hierarchy should be law, and then subsequently followed by some additional general legal act -if there is a real and justified need. The long-standing lengthy debate on the coordinating mechanism establishment ended in an unconstitutional Decision on the European integration process in Bosnia and Herzegovina coordinating system of January 2016. Although this Decision does have very good starting points, in reality its implementation is quite difficult due to the complicated decision-making structure in the mechanism. In order to adopt an efficient and quality coordinating mechanism in BH administrative institutions, it is necessary to amend the Constitution of B&H in accordance with this general legal act‟s normative potential. It means that the BH Ministries of Civil Affairs and of Human Rights must abolish following institutions: for Agency for Foreign Investment Promotion, Foreign Investments Improvement in B&H Agency, Market Surveillance in B&H Agency, Insurance Agency of Bosnia and Herzegovina, the Agency for Work and the employment of Bosnia and Herzegovina, the Agency for Medicinal Products and Medical Devices of Bosnia and Herzegovina, European Integration, Economic Planning Directorate and Police Bodies Coordination Directorate. The administrative affairs of these organizations will be taken over by the competent ministries. B&H Border Police, the Foreigners’ Service should become a department within the Ministry of Security. At the same time, the paper explains what should be the administrative tasks in new Ministries: of Foreign and Internal Trade, Labor and Social Policy, Economy and Agriculture, the Environment, and the Ministry of Education, Science, Culture and Sports de lege ferenda. Therefore, it is necessary to abolish, establish and reorganize Ministries and administrative organizations in order to introduce the coordinating mechanism in the constitutional and administrative-legal order of the BH institutions in accordance with the EU standards.